(untitled) (Revista de Física Médica, 2017)
Introduction. On 2013 the Spanish Medical Physics Society created the working group “Human resources in Radiophysics and Radiological Protection units” with the aim of redacting a document in which the real situation of human resources in these units were reflected. Methods and materials. A census of 114 centres and a survey was designed asking for the situation of Radiophysics and Radiological Protection units regarding human resources and functions developed. Survey was sent on November 2013 and answers were received up to February 2014. Data registered correspond to year 2013. Results. 85 answers were received (76%). The total number of Medical Physicists in those centres was 380.7, from which 210.5 (55%) worked in Radiotherapy Physics, 43.8 (12%) in Diagnostic Radiology, 31.9 (8%) in Nuclear Medicine, 68.8 (18%) in Radiological Protection and 25.7 (7%) in teaching and research. There are 286.3 Technicians that work mainly in Radiotherapy Physics. In Radiological Protection, 198 hospitals, 475 community health centres and 114 diagnostic centres are attended. The number of equipment under the supervision of these units is over 5400, 500 and 600 in the areas of Diagnostic Radiology, Radiotherapy and Nuclear Medicine respectively and there is participation in 380747 Diagnostic Radiology procedures, 4500 metabolic treatments and 87722 Radiotherapy treatments. Research and teaching area shows that most of the centres (75%) participate in training of different medical specialties and technicians (79%) and, as a mean, the working time dedicate to research is 12%. Conclusions. High participation (76%) indicates that the sample is representative enough of Medical Physics situation in our country. It’s has been assessed the need of human resources and to plan in a mid-term, the resources needed in order to attend the tasks that our specialty has assigned and it would be advisable to make a more detailed evaluation that analyzes specific needs of each centre.